2017
DOI: 10.3171/2016.9.spine16520
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious prevertebral soft-tissue inflammation and hematoma eliciting swelling after anterior cervical discectomy and fusion

Abstract: OBJECTIVE Anterior cervical discectomy and fusion (ACDF) procedures are performed to treat patients with cervical myelopathy or radiculopathy. Dysphagia is a post-ACDF complication. When it coincides with prevertebral space enlargement and inflammation, surgical site infection and pharyngoesophageal perforation must be considered. The association between dysphagia and prevertebral inflammation has not been reported. The authors investigated factors eliciting severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Fourth, the patients in Group I had type II incision that might cause more significantly elevated postoperative WBC count and severer inflammatory reactions than in Groups II and III. A previous study showed that the patients who developed PVST swelling-related complications had more elevated WBC and C-reactive proteins than those who did not have complications (36), supporting the present study. It was once reported that if a patient had three or more vertebral segments exposed, C2, C3, and C4 segments involved, blood loss of over 300 ml, operation duration exceeding 5 h, or preoperative spinal dysfunction, he/she might be more likely to have postoperative PVST swelling and respiratory tract-related complications (6).…”
Section: Discussionsupporting
confidence: 90%
“…Fourth, the patients in Group I had type II incision that might cause more significantly elevated postoperative WBC count and severer inflammatory reactions than in Groups II and III. A previous study showed that the patients who developed PVST swelling-related complications had more elevated WBC and C-reactive proteins than those who did not have complications (36), supporting the present study. It was once reported that if a patient had three or more vertebral segments exposed, C2, C3, and C4 segments involved, blood loss of over 300 ml, operation duration exceeding 5 h, or preoperative spinal dysfunction, he/she might be more likely to have postoperative PVST swelling and respiratory tract-related complications (6).…”
Section: Discussionsupporting
confidence: 90%
“…Noninfectious prevertebral soft-tissue inflammation is one of the reasons for PSTS after ACDF, and some studies suggested that local soft-tissue swelling is one of the most common reasons for dysphagia after ACDF 7,35 . According to the results, studies that hold a positive attitude found that LSA effectively alleviated PSTS within 2 weeks postoperatively 18,22,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Yagi et al found that prevertebral soft tissue edema was related to severe dysphagia and odynophagia after anterior cervical discectomy and fusion. [19] Studies showed that prevertebral soft tissue edema was associated with postoperative dysphagia that peaked at 3 to 4 days after anterior cervical spinal surgery, prevertebral soft tissue edema was considered as tissue damage. [20,21] Other studies suggested the intermittent release of retractors to minimize the injury of compression-associated tissue ischemia.…”
Section: Discussionmentioning
confidence: 99%